Soigner par la nature à la Réunion : l’usage des plantes médicinales comme recours thérapeutique dans la prise en charge du cancer - Caroline Desprès (Anthropologie & Santé)
This article analyses the profane logics underlying cancer patients’ medicinal plant consumption in the Reunion island (French department in the Indian Ocean). Care in the Réunionese context is characterized by the combined use of traditional, conventional and alternative medicines. This is particularly the case for cancer treatment. However, in the majority of cancer cases, various therapeutic means are associated with medical care. Medicinal plants play a great role in these multiple strategies. The consumption of theses plants, usually in the form of herbal tea, relies on well established knowledge and local custom. Once their cancer diagnosed, some patients may give up the use of these plants at their physician’s request while others continue using them in order to accompany the disease or help the healing process. The consumption of plants appears thus to be linked to the way patients try to subjectively involve themselves in the care process. This may signify a rupture of dependency on conventional medicine and, at the same time, an attempt of cultural reassertion in a cancer context which has reshuffled their identity references. In the profane world of the Reunion, the independent and individual use of traditional practitioner’s prescriptions (even though in line with their knowledge) reveals more autonomous care management. In both cases patients’ behaviors correspond to different disease appropriation strategies.